A Pyrimidopyrimidine Janus‐AT Nucleoside with Improved Base‐Pairing Properties to both A and T within a DNA Duplex: The Stabilizing Effect of a Second Endocyclic Ring Nitrogen. Issue 6 (17th January 2014) - Largy, Eric; Liu, Wenbo; Hasan, Abid; Perrin, David M.
Abstract Janus bases are heterocyclic nucleic acid base analogs that present two different faces able to simultaneously hydrogen bond to nucleosides that form Watson–Crick base pairs. The synthesis of a Janus‐AT nucleotide analogue, NJAT, that has an additional endocyclic ring nitrogen and is thus more capable of efficiently discriminating T/A over G/C bases when base‐pairing in a standard duplex‐DNA context is described. Conversion to a phosphoramidite ultimately afforded incorporation into an oligonucleotide. In contrast to the first generation of carbocyclic Janus heterocycles, it remains in its unprotonated state at physiological pH and, therefore, forms very stable Watson–Crick base pairs with either A or T bases. Biophysical and computational methods indicate that NJAT is an improved candidate for sequence‐specific genome targeting.